Experimental Study on Spray Characteristics of Gasoline/Hydrogenated Catalytic Biodiesel under GCI Conditions - Wenhua Yuan; Jingjing Liao; Bei Li; Wenjun Zhong (Journal of Chemistry)
The new blended fuel (gasoline/hydrogenated catalytic biodiesel) is expected to address the cold start problem under low temperature of gasoline compression ignition due to its excellent ignition performance. Additionally, its spray behavior as the combustion boundary condition could have a direct impact on the characteristics of subsequent combustion. Therefore, the objective of this study is to reveal the effects of hydrogenated catalytic biodiesel/gasoline on the spray characteristics under various ambient conditions. As a significant index of spray characteristics, the spray penetration was achieved by applying Mie scattering methods under nonevaporation and evaporation conditions on a constant volume combustion chamber. In addition, the experimental results were compared against the calculated values of the models. As demonstrated by the results, a better spray performance can be achieved by the blended fuel than diesel and hydrogenated catalytic biodiesel. In respect of spray penetration, there is almost no difference among the three fuels under the ambient temperature of 323 K. Nevertheless, the blended fuel is lower than that of hydrogenated catalytic biodiesel and diesel when the ambient temperature is 434 K and 523 K. Moreover, the blended fuel is the first to reach the stable state, and the hydrogenated catalytic biodiesel is earlier than diesel for the spray penetration. Meanwhile, the spray model is identified as suitable for the blended fuel.